Dialect inheritance and youth identity: an online ethnography study on dialect enthusiasts community on the new media platforms - Mei, Zhixing (Frontiers in Communication, 2024)
Faced with the decline of dialects, the rise of new media platforms has made young dialect enthusiasts an emerging force in maintaining language diversity. By sharing dialect content online, they enhance the dialect visibility and form a new way of communication, thereby highlighting the link between dialect inheritance and youth identity. To explore multilingual and multicultural dynamics in China amidst globalization, this study adopts the method of online ethnography, conducting interviews and participatory observation within dialect communities on platforms of WeChat and Bilibili. By analyzing the formation, register, and significance of the community, the study reveals that enthusiasts not only directly use and experience dialects online, but also create a special variety of “Internet dialect”. With the leading of pioneers and interrelationship among members, they break the identity barriers and negotiate to construct dialect knowledge, actively promoting the dialect culture within the “virtual acquaintances society”. The discussion underscores the necessity of youth engagement and new media in dialect living inheritance, aligning with but extending current understanding of dialect protection strategies, and points to the potential for the construction of a community with a shared future in cyberspace.